Impact of liquid viscosity on simplex spray drying atomizer performance - Garcia, Sebastien; Kornienko, Vassily; Jongsma, A.; Berrocal, Edouard (Journal of Food Engineering, 2026)
Spray drying, a process which is widely used in the food industry, involves the atomizations of a liquid slurry into a drying chamber to produce a powder of desired properties. Although liquid viscosity strongly influences process efficiency, few studies have examined its effect on spray characteristics for specific system designs, where previous work has been hindered by experimental/numerical challenges or focus on non-food systems. Therefore, this study experimentally quantifies the influence of liquid viscosity and atomizer geometry on the discharge coefficient, global Sauter mean diameter (SMD), and spray cone angle for multiple Delavan SDX V spray drying atomizer geometries under industrially relevant conditions. Performing measurements using water/glycerol mixtures enabled the use of advanced optical diagnostic techniques on mixtures with viscosities within the food-industry-relevant range (1–35 mPa s). Overall, we see that increasing viscosity, raises discharge rate and SMDs while reduces spray cone angle, regardless of pressure or atomizer geometry. We then perform a dimensional analysis over a large measured dataset in order to derive empirical equations linking design parameters to resulting sprays characteristics. We show that these equations are able to reliably predict (R2 > 0.97) the discharge coeficient, SMD and cone angle solely from liquid properties, operating conditions, and nozzle geometry. Alongside an extensive set of measurements, the derived correlations significantly expand predictive capabilities in the medium-to-low viscosity regimes relevant to spray drying in the food industry. These results can be directly applied in process simulations and design workflows, enhancing the precision and efficiency of industrial spray drying optimization.